Do FinTech and financial incumbents have different experiences and perspectives on the adoption of artificial intelligence?. (10th May 2021) - Zhang, Bryan Zheng; Ashta, Arvind; Barton, Mary Emma
Abstract: Although FinTechs and incumbents are applying artificial intelligence (AI) differently, they both expect that the status‐quo will likely be maintained through collaboration rather than competition. Both perceive BigTechs as a strategic threat given their AI capabilities and their entrance into financial services. Incumbents are experimenting with more different kinds of AI than FinTechs: FinTechs use the technologies for new products and services while incumbents are using them for incremental innovations to existing products and services. The incumbents expect that adopting AI will lead to a loss in jobs of 9% over the next 10 years and, because these companies represent a large percentage of the workforce (median company size surveyed has more than 10, 000 employees), this loss in jobs cannot be compensated by the 19% increase in jobs provided by existing FinTechs (median company size surveyed has less than 50 employees). AI can reduce and increase risk, and most incumbents and FinTechs agree that there will be no effect on risk at the organizational level but that there will be an increase in risk at the societal level. While both FinTechs and incumbents agree on the relative importance of legal and human hurdles and consider the biggest hurdle is related to data and regulations concerning data, FinTechs perceive these hurdles to be greater than do incumbents.